2019
DOI: 10.1186/s12881-019-0768-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of a placental Interleukin-6 genetic variant (rs1800796) with DNA methylation, gene expression and risk of acute chorioamnionitis

Abstract: Background Acute chorioamnionitis (aCA), inflammation of the placenta and fetal membranes, is a frequently reported lesion in preterm deliveries. Genetic variants in innate immune system genes such as Interleukin-6 ( IL6 ) may contribute to the placenta’s inflammatory response, thus predisposing some pregnancies to aCA. These genetic variants may modulate molecular processes such as DNA methylation and gene expression, and in turn might affect susceptibility to aCA. Curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 104 publications
0
7
0
Order By: Relevance
“…When considering genomic screening methods, one must consider the frequency at which "risk" variants exist in certain populations. For example, it has been reported that an IL6 variant associated with acute chorioamnionitis risk is only present in East Asian populations [198], and that selection in the progesterone receptor gene may have led to specific polymorphisms that underlie differential rates of progesterone-associated pregnancy complications by population [199]. Other maternal factors associated with risk of adverse pregnancy outcomes include socioeconomic status, comorbid health conditions, and smoking status.…”
Section: Sex Differences In Diagnostic and Screening Approachesmentioning
confidence: 99%
“…When considering genomic screening methods, one must consider the frequency at which "risk" variants exist in certain populations. For example, it has been reported that an IL6 variant associated with acute chorioamnionitis risk is only present in East Asian populations [198], and that selection in the progesterone receptor gene may have led to specific polymorphisms that underlie differential rates of progesterone-associated pregnancy complications by population [199]. Other maternal factors associated with risk of adverse pregnancy outcomes include socioeconomic status, comorbid health conditions, and smoking status.…”
Section: Sex Differences In Diagnostic and Screening Approachesmentioning
confidence: 99%
“…Standardized tools were used for assessing child behavior and adjusting our analyses for the major confounding factors in the association between DNA methylation and child behavior. Whether adjusting EWAS for cell heterogeneity is relevant is still debated [74,75]. Epigenetic marks are highly specific to cell types in the placenta as in other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…IL‐6 was the most focused inflammatory biomarker for OSA (Chu & Li, ; Kaditis et al, ; Kurt, Tosun, & Talay, ; Lopez‐Pascual et al, ; Popko et al, ; Shalitin, Deutsch, & Tauman, ; Wu et al, ; Zhong, Xiong, Shi, & Xu, ). IL‐6 rs1800796, a function variant located in the promoter region of IL‐6 , has been evaluated for its association with many kinds of diseases, including cancers, celiac disease, chronic HBV infection, acute coronary syndrome, ischemic stroke, periodontitis, IgA nephropathy, hip fracture, osteoarthritis, acute chorioamnionitis, etc., (Akinyemi et al, ; Amr, El‐Awady, & Raslan, ; Barartabar et al, ; Du, Gao, Zhang, & Wang, ; Eftekhari et al, ; Fernandes et al, ; Fragoso et al, ; Kaditis et al, ; Konwar, Del Gobbo, Terry, & Robinson, ; Li et al, ; Ponce de Leon‐Suarez et al, ; Tang et al, ; Wang, Chen, Zhao, Zhang, & Yu, ; Wang et al, ; Zhang et al, ; Zhang, Mao, & Sun, ; Zhao, Li, & Li, ). Although two previous studies evaluated the associations of IL‐6 rs1800796 with the development of OSA, the results were not significant, which may be caused by the relatively small sample size (Kaditis et al, ; Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%